2000
DOI: 10.1038/sj.cdd.4400682
|View full text |Cite
|
Sign up to set email alerts
|

Calphostin C-mediated translocation and integration of Bax into mitochondria induces cytochrome c release before mitochondrial dysfunction

Abstract: Calphostin C-mediated apoptosis in glioma cells was reported previously to be associated with down-regulation of Bcl-2 and Bcl-x L . In this study, we report that 100 nM calphostin C also induces translocation and integration of monomeric Bax into mitochondrial membrane, followed by cytochrome c release into cytosol and subsequent decrease of mitochondrial inner membrane potential (DCm) before activation of caspase-3. The integration of monomeric Bax was associated with acquirement of alkali-resistance. The tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 64 publications
1
27
0
Order By: Relevance
“…However, whether the release of mitochondrial factors to the cytosol is the cause or a consequence of the decrease in ⌬⌿m remains to be elucidated. For example, several studies have shown that a loss in ⌬⌿m precedes cytochrome c release (32,33), whereas other studies have shown that cytochrome c release occurs prior to mitochondrial membrane potential loss (34). The present data support the latter view, since in the neuroprotective effect of NMDA (and also K25), the blockade of the release of Smac/DIABLO and cytochrome c is observed before the recovery of the mitochondrial membrane potential.…”
Section: Discussionsupporting
confidence: 79%
“…However, whether the release of mitochondrial factors to the cytosol is the cause or a consequence of the decrease in ⌬⌿m remains to be elucidated. For example, several studies have shown that a loss in ⌬⌿m precedes cytochrome c release (32,33), whereas other studies have shown that cytochrome c release occurs prior to mitochondrial membrane potential loss (34). The present data support the latter view, since in the neuroprotective effect of NMDA (and also K25), the blockade of the release of Smac/DIABLO and cytochrome c is observed before the recovery of the mitochondrial membrane potential.…”
Section: Discussionsupporting
confidence: 79%
“…However, unlike druginduced, Bax-dependent death of cells of epithelial origin (54), it seems that caspase activity is not required for As 2 O 3 -induced neuroblastoma cell death. Thus, our results suggest a Baxdependent, but caspase-independent, cell death mechanism caused by As 2 O 3 , which also has been reported to occur with other drugs in other cell systems (55,56).…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, it is impossible to exclude that there is some other, still unknown oligomycin target responsible for the observed antiapoptotic effect of the antibiotic. This is hardly Bax oligomerization (Ikemoto et al, 2000) since, if it were the case, the Sts-induced apoptosis would also be oligomycin-sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of antiapoptotic action of oligomycin have also been suggested. It was reported to block dimerization of Bax (a pro-apoptotic Bcl-2 family member) and following cytochrome c release involved in the calphostin C-induced apoptosis (Ikemoto et al, 2000). Inhibition of cytochrome c release by oligomycin was also inherent in some Bax-independent apoptoses (Matsuyama et al, 1998;Goldstein et al, 2000).…”
Section: Introductionmentioning
confidence: 99%